Nuclear Forces in the Medium: Insight From the Equation of State - Sammarruca, Francesca; Millerson, Randy (Frontiers in Physics, 2019)
In this review, we concentrate on recent efforts of our group aimed at investigating the nuclear equation of state of symmetric nuclear matter (equal concentrations of protons and neutrons) and the one of pure neutron matter. Although idealized, these systems are suitable “laboratories" to probe nuclear forces in the many-body system. The energy per particle as a function of density can reveal rich information about the nature of nuclear forces in the medium and how they impact observable properties. For instance, the pressure in neutron-rich matter has been found to have profound impact on very diverse systems, ranging from the thickness of the neutron skin in a heavy nucleus to the properties of compact stars. The current trend in nuclear physics is to build few-nucleon forces according to the prescription of chiral effective field theory. We open by reviewing in depth how we develop equations of state based on state-of-the-art chiral interactions. We then highlight some applications in neutron-rich nuclei and neutron stars.